2021
DOI: 10.1093/ajh/hpab135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Video-Assisted Patient Education Program to Reduce Blood Pressure Delivered Through the Electronic Medical Record: Results of a Quality Improvement Project

Abstract: BACKGROUND Low-cost, automated interventions that increase knowledge and skills around diet and lifestyle modifications are recommended for cardiovascular disease risk reduction. METHODS We initiated a quality improvement program to assess the impact of a web-based diet and lifestyle intervention utilizing short animated videos in adults with high blood pressure (BP) at a primary care clinic in Saudi Arabia. We enrolled adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Further, using apps can also create a social network among hypertensive patients, allowing them to exchange information, improve mood, and reduce stress ( Mugabirwe et al, 2021 ). A meta-analysis reported that video-assisted patient education materials improve cardiovascular disease prevention behaviors and that use of them as a support tool for hypertension management significantly improves patient follow-up ( Miller et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, using apps can also create a social network among hypertensive patients, allowing them to exchange information, improve mood, and reduce stress ( Mugabirwe et al, 2021 ). A meta-analysis reported that video-assisted patient education materials improve cardiovascular disease prevention behaviors and that use of them as a support tool for hypertension management significantly improves patient follow-up ( Miller et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, trust is often contingent upon patients' full understanding of medical procedures; insufficient or ineffective communication may lead to distrust [4]. The elderly population tends to exhibit higher levels of distrust compared to younger groups [5].…”
Section: Elderly 'S Trust To Medical Advicementioning
confidence: 99%
“…This not only improves training efficiency, but also ensures that the healthcare workforce is ready to fully adopt RME. In turn, this will result in more precise and precise patient data, as well as better healthcare processes overall (Miller et al, 2021). Hospitals can ensure that their medical teams are skilled in using the latest technology by utilizing video media in the RME learning context (Zoghbi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%